EFFECTIVENESS OF EDTA DIPS ON THE SHELF-LIFE OF OIL SARDINE (SARDINELLA LOMGICEPS ), MACKEREL (RASTRELLIGER KANAGURTA) AND PRAWN (METAPENAEUS DOBSONI) IN ICE STORAGE - SURENDRAN, P K; IYER, K MAHADEVA; GOPAKUMAR, K (Fishery Technology, 2017)
FreshÂ·Â·oil sardine, mackerel and prawn were dipped in 0.1% and 1% solutions of Na2EDTA, and stored in ice. Their storage-life was assessed by bacteriological, chemical and sensory methods. Eventhough EDTA treatment controlled the increase in bacterial counts and reduced TMA and TVBN production in oil sardine and mackerel, the consequent beneficial effect was not realised because of the deterioration of fat in these fishes, leading to rancidity. But, for prawn stored in ice, a dip in 1% solution of Na2EDTA enhanced the shelf-life by at least 8 days over the untreated control. EDTA absorbed by the muscle of fish and prawn during dip in Na2EDTA solution is not completely removed during their iced storage for 25 days.